KERETAKAN RUMAH TANGGA AKIBAT PERILAKU MEROKOK: ANALISIS PUTUSAN PENGADILAN AGAMA DEPOK NO. 4245/PDT.G/2018/PA.DPK DALAM PERSPEKTIF MAQASHID SYARIAH - Fadhilah Khairul Anam; Musyafi Usman (USRAH: Jurnal Hukum Keluarga Islam, 2025)
An ideal marriage is one that can create a harmonious, loving, and merciful family. However, this goal can be hindered when behaviors arise that disrupt comfort and harmony, such as the habit of smoking. Smoking by one of the spouses has the potential to cause conflicts that may trigger divorce, as seen in the Depok Religious Court Decision No. 4245/Pdt.G/2018/PA.Dpk. This study aims to analyze the trial facts and the judge’s considerations in the decision from the perspective of maqashid sharia, in order to identify the extent to which the decision reflects the protection of public interest, prevention of harm, and fulfillment of the main objectives of marriage. The study uses a qualitative method with a normative juridical approach. The results indicate that the juridical basis for divorce in this case refers to broken marriage, in accordance with Article 116 letter f of the Compilation of Islamic Law. The trial facts show relevance to this juridical basis and are also related to maqashid sharia, as they contain elements of harm threatening the five aspects of sharia protection. The judge’s consideration to grant the divorce appears aligned with the essence of maqashid sharia, namely promoting benefit and preventing greater harm. The loss of tranquility, affection, and mercy due to smoking behavior has damaged the primary objectives of marriage, making divorce an appropriate step to restore the benefit.